2010
DOI: 10.1080/03067310902871299
|View full text |Cite
|
Sign up to set email alerts
|

Parametric evaluation for programmable temperature vaporisation large volume injection in gas chromatographic determination of polybrominated diphenyl ethers

Abstract: This work is a thorough investigation on the major operating parameters of the programmable temperature vaporization (PTV) inlet used for gas chromatographic injection, including injection mode and volume, inlet temperature, vent and purge flow rates. The results clearly demonstrate the advantage of large volume injection in enhancing the detection of polybrominated diphenyl ethers (PBDEs). Partial loss of injected PBDEs occurred during solvent venting and due to incomplete sample transfer. Such loss was minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…To attain better sensitivity, Wei et al investigated different operating parameters of a programmable temperature-vaporization (PTV) inlet used in GC injection and enhanced PBDE detection by injecting 120 lL of sample solution [75]. The technique was illustrated by testing indoor dust SRM 2585, sediment, and placenta-tissue samples, and results demonstrated that PTV-GC-ECNI-MS was a sensitive, reliable approach for testing extremely low levels of PBDEs.…”
Section: Trendsmentioning
confidence: 98%
“…To attain better sensitivity, Wei et al investigated different operating parameters of a programmable temperature-vaporization (PTV) inlet used in GC injection and enhanced PBDE detection by injecting 120 lL of sample solution [75]. The technique was illustrated by testing indoor dust SRM 2585, sediment, and placenta-tissue samples, and results demonstrated that PTV-GC-ECNI-MS was a sensitive, reliable approach for testing extremely low levels of PBDEs.…”
Section: Trendsmentioning
confidence: 98%
“…A total of 49 PBDE congeners and DBDPE were analyzed on an Agilent 6890 gas chromatograph (GC) coupled with a 5973N mass spectrometer (MS) with electron capture negative ionization (ECNI). GC/MS parameters were optimized in our previous studies. , The MS was operated in selected ion monitoring (SIM) mode with m / z 486.6 and 488.6 for BDE209, 79, and 81 for other PBDEs, DBDPE, and BB209, and 510 and 512 for PCB209L.…”
Section: Methodsmentioning
confidence: 99%
“…GC/MS parameters were optimized in our previous studies. 21,22 The MS was operated in selected ion monitoring (SIM) mode with m/z 486.6 and 488.6 for BDE209, 79, and 81 for other PBDEs, DBDPE, and BB209, and 510 and 512 for PCB209L.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The PTV operational parameters were optimized for PBDE analysis. [9] The initial oven temperature was 90 • C, which lasted for 3 min, and then increased to 140 • C at 10 • C/min and further to 300 • C at 5 • C/min. The final temperature was kept for 15 min until the run was completed.…”
Section: Laboratory Analysesmentioning
confidence: 99%